Magnetic resonance imaging of endolymphatic hydrops in Ménière's disease: A comparison of the diagnostic value of multiple scoring methods - Xiao, Heng; Guo, Xiaojing; Cai, Huimin; Lin, Jianwei; Lin, Chenxin; Fang, Zheming; Ye, Shengnan (Frontiers in Neurology, 2022)
Objectives: To compare three methods of scoring endolymphatic hydrops in patients with Ménière's disease in order to assess the correlation between endolymphatic hydrops and auditory characteristics. Methods: A retrospective study of 97 patients with unilateral definite Ménière's disease(DMD) who underwent contrast-enhanced three-dimensional fluid attenuated inversion recovery (3D FLAIR) MRI. Each patient was scored by the Inner Ear Structural Assignment Method (IESAM), the Saccule to utricle area ratio (SURI), and the Four Stage Vestibular Hydrops Grading (FSVH), according to their corresponding axial images. Cohen's Kappa and intra-class correlation coefficient were used for consistency testing, combined with binary logistic regression analysis, to compare the sensitivity and specificity of the three methods. The degree of hydrops in different stages of MD was compared. The correlation between endolymphatic hydrops in the inner ear sub-units and hearing thresholds was further analyzed. Results: The intra- and inter-reader reliability for the scoring of endolymphatic hydrops were excellent. The IESAM had a high diagnostic value for identifying definite Meniere’s disease(sensitivity: 86.6%, specificity: 97.9%). The hearing thresholds were correlated with the degree of endolymphatic hydrops. Stages 3 and 4 were more significant for the severity of hydrops than stage 1. Within the subgroups of the Meniere's disease patients, compared with the non-hydrops group and the pure vestibular hydrops (V group), the cochlear combined vestibular hydrops group (CV group) had significantly higher auditory thresholds. The amplitude ratio of electrocochleogram was significantly higher in the affected ear than in the healthy ear. Conclusion: The IESAM is a more sensitive and specific diagnostic scoring method for the diagnosis of DMD. Diagnostic imaging may improve the detection of inner ear hydrops which is correlated with severity of hearing loss. A comprehensive evaluation of the inner ear sub-unit structures maybe necessary. Comparison of scoring methods for MD.